Eksplorasi Kemampuan Berpikir Kritis Matematika Berdasarkan Keyakinan (Belief) Siswa - Imaludin Agus; Amiluddin Nur Purnama (Jurnal Tadris Matematika, 2022)
This study aims to explore students' mathematical critical thinking skills based on belief at SMPN Satu Atap 1 Kabawo. This research is descriptive exploratory. The research subjects were students of class VIII for the 2020/2021 academic year. The instruments used in data collection were test of students’ critical thinking skills, questionnaires on students’ beliefs about mathematics, and interview guidelines. The data collected was then analyzed descriptively. The results showed that the percentage of students' confidence of mathematics in the medium category was 61.12%, the percentage of students’ confidence of mathematics in the high category was 25%, and about 13.88% of students’ confidence of mathematics was in the low category. Students with high confidence showed a tendency to be able to solve critical thinking skills in the aspects of interpretation, analysis, and evaluation. Students with moderate confidence tend to be able to solve problems in the aspects of interpretation and evaluation, while students with low categories have not been able to solve problems in all aspects of critical thinking skills.